From KL to Beijing: MH370, the media and the meaning of a disaster - Halim, Rohizah (Elsevier Ltd., 2014)
News texts are the product of journalistic practices and organizational routines, buttressed by socio-cultural norms of a particular society.The tragedy of flight MH370 is a way to understand how Malaysian media construct a crisis that last happened in 1977. To understand how Malaysian newspapers understood the event, a critical discourse analysis approach is applied to two newspapers.News organizations in Malaysia – as baffled by the event as the officials and starved of information – construct their own meaning of the air disaster.This study concludes that newspapers construction of the tragedy reveal the socio-cultural make-up of news production practices.